مكانة الضحية في ظل النظام الأساسي للمحكمة الجنائية الدولية الدائمة - عمراوى، خديجة (جامعة غرداية, 2018)
تهدف هذه الدراسة إلى إبراز دور المحكمة الجنائية الوقائي، والذي يمنع أو يحد من حالات انتهاك أحكام القانون الدولي الجنائي، وهو أمر سيسهم إلى حد كبير في التقليل من ارتكاب هذه الجرائم الدولية أو على الأقل يخفف من فظاعتها. وبالرغم من الجهود الدولية التي بذلت في إطار القانون الدولي الجنائي من أجل تمكين ضحايا الجرائم الدولية من استيفاء حقوقهم التي أقرها لهم القانون والتي شملت مجالي الاختصاص والإجراءات أمام المحكمة الجنائية الدولية، إلا أن هناك عقبات تتعلق هي الأخرى بمجالي الاختصاص والإجراءات ما زالت تحول دون تمكنهم من استيفاء حقوقهم التي أقرها لهم القانون الدولي الجنائي.
This study aims to highlight the role of the preventive criminal court, which prevents or limits cases of violation of the principles of international criminal law, which will contribute significantly to reducing the commission of these international crimes, or less dilute the horror. Despite the international efforts that have been made under international criminal law to enable victims of international crimes to meet their rights as approved by their legislation, and which included the areas of jurisdiction and procedure before the international criminal court but there are obstacles related to the areas of jurisdiction and procedures that are still going on without allowing them their rights approved by their international criminal law.
Keywords: المحاكم الدولية -- المسؤولية الجنائية -- الاتفاقيات الدولية -- حقوق الإنسان